Saskatchewan Teacher Activists’ Perceptions of Union and Grassroots Activism - Keil, Trudy (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Amid the global neoliberal assault on public education, teachers and their unions are called upon to resist detrimental educational reforms. Employing photo-elicitation focus groups, this paper explored ten Saskatchewan teacher activists’ perceptions of their political resistance to neoliberalism both within their union and beyond. Utilizing a comparative case study approach, the study employed a poststructural framework of alliances, assemblages, and affect to analyze teachers’ intellectual and emotional views. Intellectually, teachers agreed that the teacher union was less responsive than grassroots activism because of their diverse membership and legislative requirements. Teachers expressed that, despite seemingly insurmountable obstacles, they valued equity, activism, mentoring, and group collectivity. Emotionally, teachers exuded feelings of anger and isolation, but also hope and empowerment rooted in learning. Featuring teachers' metaphorical interpretations, this paper delves into teachers’ affective understandings of their activism as a potential antidote to neoliberalism.